Location-Based Mode Selection and Resource Allocation for Device-to-Device Underlay Communication - Jun Yao; Qing Huang (Dianxin kexue)
Device-to-device（D2D）communication underlaying cellular networks can bring great benefits to spectrum resource utilization and users' throughput. However, because of the interference caused by D2D communication, interference cancellation and coordination becomes very important. A joint mode selection and resource allocation scheme was proposed to improve the performance of system in the downlink direction. Simulation results show that, compared to pure greed D2D scheme and cellular scheme, the proposed scheme can achieve higher system throughput.